MEMBANGUN HARMONI LEWAT KEBERSAMAAN: STUDI KASUS DAMPAK SOSIAL PENENTUAN AWAL RAMADHAN DAN 1 SYAWAL TERHADAP UMAT ISLAM DI KOTA PADANG - Zaenal Abidin (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
This research was aimed to explore more about the social impact caused by the initial determination of Ramadhan and 1st Syawwal towards the Muslims in Padang. Sociologically the city of Padang is composed of various groups of society and though relatively modern, of course the phenomenon of many congregational groups had no diversity and enlivening the community, particularly in the Muslim community. So far here is to trace how much the positive and negative impact toward Muslims society on the difference in the initial determination of Ramadan and 1st Syawal.